The roles of sirtuins in ferroptosis - Zeng, Jieqing; Guo, Junhao; Huang, Si; Cheng, Yisen; Luo, Fei; Xu, Xusan; Chen, Riling; Ma, Guoda; Wang, Yajun (Frontiers in Physiology, 2023)
Ferroptosis represents a novel non-apoptotic form of regulated cell death that is driven by iron-dependent lipid peroxidation and plays vital roles in various diseases including cardiovascular diseases, neurodegenerative disorders and cancers. Plenty of iron metabolism-related proteins, regulators of lipid peroxidation, and oxidative stress-related molecules are engaged in ferroptosis and can regulate this complex biological process. Sirtuins have broad functional significance and are targets of many drugs in the clinic. Recently, a growing number of studies have revealed that sirtuins can participate in the occurrence of ferroptosis by affecting many aspects such as redox balance, iron metabolism, and lipid metabolism. This article reviewed the studies on the roles of sirtuins in ferroptosis and the related molecular mechanisms, highlighting valuable targets for the prevention and treatment of ferroptosis-associated diseases.